Turkish State Railway : Options for Reform - World Bank (World Bank, Washington, DC, 2017)
During the 1990s, the Turkish economy was beset by frequent economic crises. Fiscal imbalances, high inflation rates, and the subsequent stop and go economic cycles hit the Turkish economy, slowing growth and plunging the country into recession. Spiraling debt and interest payments coupled with failures in financial systems resulted in significant financial crises in late 2000 and early 2001. The Government of Turkey initiated a number of economic reforms to contain spending, cut its deficit, reduce inflation, and provide a basis for renewed economic growth. The Government has mapped out a structural reform program encompassing measures to address the biggest sources of fiscal deficits, strengthen the legal and regulatory frameworks, and accelerate the privatization of the remaining state enterprises. Reform of the Turkish State Railways (TCDD) is one of the main targets for change. Over the past few decades, TCDD has fallen into a financial crisis from which it will not be able to emerge without a dramatic restructuring of its governance and organization. TCDD operates the state railway, the seven largest ports, and manufactures and repairs locomotives, wagons and passenger coaches. As an enterprise, TCDD is the largest money loser among Turkey’s public sector enterprises.